Playgrounds and play areas and their equipments / Shamaruddin Hj. Ismail - Ismail, Shamaruddin (Faculty of Architecture, Planning and Surveying, 1979)
The purposes of playgrounds and play areas, together with their equipments, are to provide children, who are the intended users, with places and facilities with which they could develop their mentality and creativity, while playing. It is within these playgrounds that children could learn all about their surroundings and learn how to play, and then, ultimately, learn how to cooperate with all the other young children.' Children, as is very apparent, are increasingly more receptive and therefore gain knowledge very quickly, with each new generation. Their thirst for knowledge seems to have no end. Playgrounds and play areas, in this case, play a very important role in quenching this thirst…